中國文化中的人論與醫學: 儒家之醫學模式: Humanity and Medicine in Chinese Culture: A Confucian Medical Model - LEE, Shui Chuen (International Journal of Chinese & Comparative Philosophy of Medicine, 2015)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 西方醫學界近年有學者提出新的「生物心理社會精神」醫藥模式以回應西方現代醫藥模式的問題。本文首先指出西方傳統之以醫藥為針對身體的正常功能之失效為主，而此一失能是身體之物理生理的表現，因而其他心理或精神的病狀或病態都必須能化約為身體的物理生理情狀，才被認可為疾病。此自然排除了心理或精神，以及由社會宗教價值失調而來的疾病。雖然此模式需要修訂，但此缺失不足以重新引入宗教教義作為診治疾病的判準。本文同時檢討了西方醫學以物種正常功能作為疾病的判準，以及近年流行的「實證醫學」政策診治模式所延續與隱含的仍然是以物理生理為主的醫藥模式，並不真能包含源自文化與價值的心理與心靈的疾病或病態。 由於文化與價值的不同，中醫的醫藥模式與西方醫學不同。中國哲學以人為與天地萬物同出一源，人的生命與宇宙相對應，因此，疾病被理解為人身之小宇宙失調，而治療則以順大自然的運行法則而行。這是建立在中國傳統的儒與陰陽五行的哲學而來。儒家哲學以仁心貫通天人，因而中醫自始即不限於氣化流行的現象，而有深入了解天道運行的意義，視人為與宇宙一體的生命，身體官能之運作與宇宙之陰陽五行之氣化相應，而其中以仁心之天道貫通疾病與醫病之關係，構成中醫之儒醫理念與「醫乃仁術」的模式。心靈與心理的疾病有不同的病源和對治的方式，不能化約為物理生理的情況。在此模式中，社會文化與價值失調的疾病和病態可以被正視和治療，這亦反映了醫藥乃是文化的一環。 A new conception of medicine has been proposed in response to some of the problems of the modern Western model of medicine. In this paper, I posit the view that modern Western medicine takes disease to be a bodily deviation from normal species functioning. Such malfunctioning is regarded as of the physical and physiological kind. Other types of deviations such as psychological or spiritual deviations must be reducible to symptoms before they are regarded as a disease in medical terms. Hence, psychological or mental disorders resulting from social or religious values are not catalogued as diseases, and are thus left untreated. I argue, however, that although this situation needs correction, there is no justification for introducing religious doctrine as a category of disease. This paper examines the presuppositions of the normal species functioning criterion and recent trends in evidence-based medicine, and reaches the conclusion that the present Western medical model does not readily admit some of the diseases of the human psyche caused by disorders in culture and values. Chinese medicine, which is grounded in a different culture and different values, takes a different approach to medicine. Chinese philosophy takes human beings to have the same source as the universe, and thus to represent the cosmos writ small. Disease is regarded as a disorientation of the bodily cosmos, and treatment is basically a restoration of the body and mind as a whole in harmony with natural cosmological operations. Chinese philosophy draws on Confucianism, Daoism, and the Yin-Yang School. Confucianism views empathy as unifying human beings with Heaven. Thus, in Chinese medicine the evolutionary process of the cosmos bears deeply humane and transcendental values. The correspondence between body and universe results in a conception of medicine as the operation of the principle of ren, or humanity. Accordingly, the physician is honored as a Confucian doctor, and medicine is seen as an art or humanity. Mental and psychological diseases can have independent sources, and should never be reduced to the physical and physiological. In the Chinese model, social, cultural, and value disorders are regarded as proper diseases, and can be treated as such. It allows full realization of the cultural factors at play in medicine. DOWNLOAD HISTORY | This article has been downloaded 895 times in Digital Commons before migrating into this platform.